PENGARUH LINGKUNGAN KERJA DAN KARAKTERISTIK INDIVIDU TERHADAP KINERJA KARYAWAN PT. BANK PEMBANGUNAN DAERAH SUMATERA BARAT CABANG BUKITTINGGI - Riche Fermayani (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2016)
This research aims to identify influence of the job environment (X1) and the individualcharacteristics (X2) influence the level of employees performances (Y). This research wasconducted at employees at Regional Development Bank Bukittinggi Branch with 40 samples. Thetechnique to determine samples was total sampling. It means populations to be samples. Analysis ofthe data used in this study is the method of multiple linear regression, whereas for hypothesistesting using partial test (t-test), simultaneous test (f-test), reliability test, validity test and thecoefficient of determination test (R2).From this results of this study is to show that influence of thejob environment and the individual characteristics has the ability to affect performances felt byemployees of Regional Development Bank Bukittinggi Branch of 0,12%. The coefficient determinedtest (R2) explained that influence of the job environment and individual characteristics had affect of21,4% to employees performances, while the rest, which is 78,6% was described by other variablesfrom this study.Key word: Influence of the job environment, the individual characteristics and employeesperformances.